The Implementation of Role Play Method for Improving Speaking Skills in Grade 11 at SMAN 1 Kisaran - Panjaitan, Ruth; Sri Rahayu (Universitas Negeri Medan, 2025)
This research explores how role play activities can transform English speaking skills among Grade 11 students at SMAN 1 Kisaran. The study was conducted using a quasi-experimental design with 60 students divided into experimental and control groups over 8 weeks. The experimental group participated in structured role play sessions three times per week, engaging in scenarios like restaurant conversations, job interviews, and shopping dialogues. Data was collected through pre-tests, post-tests, classroom observations, and confidence surveys. The findings show remarkable improvements: students in the role play group increased their speaking fluency by 38%, accuracy by 35%, pronunciation by 29%, and confidence by 42% compared to the control group. The research demonstrates that role play creates an engaging, low-pressure environment where students naturally develop their speaking skills by